DETERMINING THE UNIQUE MICRO-EXPLOSION MECHANISM OF EMULSIFIED BIODIESEL FUEL PARENT DROPLET - ABD SALIM, AMIRUL (2018)
The presence of water in biodiesel is a promising strategy that can decrease the development of NOx and PM emissions at the same time. One of the method that were used is water-in-biodiesel emulsion (WiBE). This technique enhances fuel efficiency and reduces emission of hazardous pollutants from diesel engines. Although numerous studies on water-oil-emulsion are available, the reports on biodiesel emulsion break-up mechanism are still incomplete. The present study aims on identifying the parameters of the biodiesel emulsion which influence the occurrence of micro-explosion such as droplet size, hydrophilic lipophilic balance value, water content and surfactant concentration. This study also visualizes and record the evolution of micro-explosion for the optimised biodiesel emulsions based on different characteristics such as type of emulsion, density, viscosity and water droplet size at different droplet heating temperatures.